(untitled) (Research, Society and Development, 2021)
The objective of this work was to analyze the challenges of humanization insertion in undergraduate courses in the health area. This is an integrative review of articles indexed in MEDLINE, LILACS, BDENF, Scopus and Google Scholar databases, from 2010 to 2020. The combination of the following controlled descriptors was used in Portuguese and English: Docente/Teaching, Humanização/Humanization, Ensino/Faculty and Saúde/Health. We included 15 studies developed in Brazil, Chile and Colombia. From the full reading of the articles, three more frequent themes emerged: challenges of humanization in the health area, challenges of humanization in teaching- learning and challenges of humanization in teaching work. The concept of humanization for teachers and students in the health area is related to the comprehensive approach of care in care, experienced in the act of clinical practices, associated with the processes of empathy and welcoming, which rescues the human dimension. Although the curricularization of humanization in undergraduate courses is a trend, there are challenges that prevent it from happening fully, such as work overload and the scarcity of practical classes, generating unfavorable consequences during graduation and student education.